Population dynamics of 3 Acartia species (Copepoda, Calnoida) in Thau lagoon, South of France - Boyer, Severine (2009)
Several species of Acartia spp. coexist in the Thau lagoon, South of France. This study presents the first record of Paracartia grani in this lagoon. Population dynamics, egg production and hatching success of 3 congeneric species (A. clausi, A. discaudata and P. grani) have been followed over a year at a monitoring station. While A. clausi and A. discaudata are perennial, P. grani is observed from June to December. Maximum egg productions of A. clausi and A. discaudata were observed in winter ranging between 20 and 30 egg.fem-1 d-1 whereas P. grani’s highest egg production occurred in autumn and averaged 12 egg.fem-1 d-1 . While the three species are known to produce resting eggs, A. clausi was the unique species presenting twice hatching success ≤ 50%. Identification of stages of development together with prosome length measurements have enabled us to determine between 4 and 6 in situ generations for these targeted species. Acartia spp. biodiversity and population dynamics have been compared on the long term using unpublished datasets collected since the 30ies at the monitoring station. Results show that the Acartia spp. community structure has changed over the last 60 years and that temperature was not responsible for this change. P. grani has appeared at the monitoring station while A. latisetosa and A. bifilosa are no longer recorded.